Pelatihan Konvensi Hak Anak Kabupaten Tebo Provinsi Jambi - Agus Santoso; Trie Hierdawati; Nurdin Nurdin; Esti Susilawati (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
The Convention on the Rights of the Child is an instrument that formulates universal principles and legal norms regarding the status of children, which aims to uphold the principles of recognition of the inherent dignity and equal rights of children who are recognized as human beings and is the basis for freedom, justice and peace with an agreement to ensure that children's basic needs are met.